2009
DOI: 10.1111/j.1469-7610.2008.01982.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological regulation of stress in referred adolescents: the role of the parent–adolescent relationship

Abstract: Background: Psychopathology in youth appears to be linked to deficits in regulating affective responses to stressful situations. In children, high-quality parental support facilitates affect regulation. However, in adolescence, the role of parent-child interaction in the regulation of affect is unclear. This study examined physiological reactivity to and recovery from stress in adolescents at risk for psychopathology, and their associations with internalising and externalising problems and parent-adolescent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 32 publications
0
33
2
2
Order By: Relevance
“…Furthermore, children with high levels of externalizing symptoms have evidenced diminished RSA suppression to stressors (Boyce et al 2001;Calkins et al 2007) while individuals higher on both externalizing and internalizing symptoms showed exaggerated RSA suppression (Calkins et al 2007); null findings have also been reported (e.g., Dietrich et al 2007). Similar, mixed findings have been reported for adolescents; in a recent study it was found that as externalizing symptoms increased, RSA suppression decreased but only for children low in parental attachment security (Willemen et al 2009). Across several age groups, children diagnosed with clinical levels of externalizing problems have exhibited similar levels of RSA suppression to matched control children (Beauchaine et al 2007).…”
mentioning
confidence: 67%
“…Furthermore, children with high levels of externalizing symptoms have evidenced diminished RSA suppression to stressors (Boyce et al 2001;Calkins et al 2007) while individuals higher on both externalizing and internalizing symptoms showed exaggerated RSA suppression (Calkins et al 2007); null findings have also been reported (e.g., Dietrich et al 2007). Similar, mixed findings have been reported for adolescents; in a recent study it was found that as externalizing symptoms increased, RSA suppression decreased but only for children low in parental attachment security (Willemen et al 2009). Across several age groups, children diagnosed with clinical levels of externalizing problems have exhibited similar levels of RSA suppression to matched control children (Beauchaine et al 2007).…”
mentioning
confidence: 67%
“…Indeed, a fair number of studies have found that children with externalizing behavior problems display a more blunted vagal response to challenge (Beauchaine, 2001; Boyce et al, 2001; Calkins & Dedmon, 2000; Musser et al, 2011). On the other hand, some studies have failed to find a link between RSA withdrawal and externalizing problems (Beauchaine, Gatzke-Kopp, & Mead, 2007; Eisenberg et al, 2012; Erath, Tu, & El-Sheikh, 2011) with such a link further attenuated by the presence of co-occurring internalizing problems (Calkins, Graziano, & Keane, 2007) or only occurring in the presence of a moderating environmental factor such as attachment status (Willemen, Schuengel, & Koot, 2009). …”
Section: Vagal Withdrawal and Externalizing Behavior Problemsmentioning
confidence: 99%
“…Studies vary on how RSA is quantified with some using spectral analysis (Miskovic, Schmidt, Georgiades, Boyle, & MacMillan, 2009; Scheinin et al, 1999; Wolff, Wadsworth, Wilhelm, & Mauss, 2012) while others use time-domain peak valley analysis (El-Sheikh & Whitson, 2006; Hinnant & El-Sheikh, 2009; Willemen et al, 2009) or the Porges adaptive polynomial filter method (Calkins et al, 2007; Graziano, Keane, et al, 2007; Hastings, Nuselovici, et al, 2008; Porges et al, 1996). The Society for Psychophysiological Research’s Task Force committee concluded that no single measure for quantifying RSA can be viewed as the gold standard as each of approaches offers advantages and disadvantages (Berntson et al, 1997).…”
Section: Measurement Issues Associated With Rsamentioning
confidence: 99%
“…Research on childhood (e.g., Raikes & Thompson, 2008) and adolescence (e.g., Willemen, Schuengel, & Koot, 2009) clearly supports this supposition but less is known about aspects of close relationships and their origin in adulthood and older age (Merz, Schuengel, & Schulze, 2007). This is unfortunate because adult relationships, especially the pair bond between romantic partners, can be an important resource in dealing with life"s challenges such as aging, declining health and shrinking social networks.…”
Section: Introductionmentioning
confidence: 95%